Potential efficacy of processing technologies for mitigating crustacean allergenicity. Issue 17 (25th September 2019) - Khan, Mati Ullah; Ahmed, Ishfaq; Lin, Hong; Li, Zhenxing; Costa, Joana; Mafra, Isabel; Chen, Yan; Wu, Yong-Ning
ABSTRACT: Crustacean allergy has become a growing food safety concern at a global scale. In the past decades, various food processing approaches have been employed to develop food products with reduced allergenic potential. Thermal treatment can dramatically influence the allergenicity of crustaceans by either reducing or enhancing their allergenic potential. Maillard reaction, enzymatic and acid treatments have shown to be promising in mitigating crustacean allergenicity. Recently, novel processing technologies, namely high-pressure processing, high-intensity ultrasound, irradiation, pulsed ultraviolet light and hurdle technology have attracted special attention from the researchers and the food industry professionals owing to their benefits over the conventional methods. In this context, this review paper provides an updated overview of the current knowledge on how different food processing methods induce structural changes of crustacean allergens and, subsequently, influence their allergenic potential. Data on prevalence and clinical relevance of crustacean allergy are presented, as well as, the molecular characterization of crustacean allergens and the main analytical methods for their detection in processed foods.